2015
DOI: 10.1007/s00404-015-3913-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and toxicity profile of pegylated liposomal doxorubicin in patients with advanced ovarian cancer

Abstract: In conclusion, this retrospective study showed the efficacy and low toxicity of pegylated liposomal doxorubicin in patients with advanced EOC. Further observations are needed to confirm these preliminary experiences on a larger number of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In the PLD monotherapy group, ORR and CBR were 5.0% and 17.5%, respectively. Table 4 presents a comparison of efficacy of PLD monotherapy with different studies [ 11 14 15 ], and the results of this study are poorer than those of other studies. While the average number of previous chemotherapy regimens of other studies was less than 2, the patients in the present study had an average of 3.5 previous chemotherapy regimens; the marked difference in this basic factor appears to have affected the response rate.…”
Section: Discussionmentioning
confidence: 90%
“…In the PLD monotherapy group, ORR and CBR were 5.0% and 17.5%, respectively. Table 4 presents a comparison of efficacy of PLD monotherapy with different studies [ 11 14 15 ], and the results of this study are poorer than those of other studies. While the average number of previous chemotherapy regimens of other studies was less than 2, the patients in the present study had an average of 3.5 previous chemotherapy regimens; the marked difference in this basic factor appears to have affected the response rate.…”
Section: Discussionmentioning
confidence: 90%
“…The main toxicities that may occur in AOC patients treated with PLD chemotherapy regimen are nausea, palmar-plantar erythema or hand-foot syndrome, stomatitis, and myelosuppression. [34] Some recent studies showed that the PLD + carboplatin chemotherapy regimen had significantly higher incidence of anemia and thrombocytopenia, and AOC patients receiving PLD + carboplatin chemotherapy regimen had higher incidence of experiencing dose delays than those in the standard treatment arm and may had discontinued treatment because of toxicity or refusal. [35] Accordingly, PLD + carboplatin chemotherapy regimen showed more nonhematologic toxicity for AOC patients.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Although the most extensive data exist on the development of leukemia in patients with Hodgkin's disease treated with chemotherapy, there are a number of other malignancies for which systemic treatment leads to a second primary cancer at a frequency greater than would be expected in the general population. 2 Pegylated liposomal doxorubicin (PLD) is a liposomal encapsulated form of the chloride salt of doxorubicin [3][4][5] that is currently approved for the treatment of recurrent epithelial ovarian cancer, Acquired immunodeficiency syndromerelated Kaposi's sarcoma, desmoid tumor, and metastatic breast cancer. 6,7 PLD has good tolerability demonstrated in both prospective and retrospective studies and a favorable safety profile compared to conventional doxorubicin, which is associated with cardiotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 PLD has good tolerability demonstrated in both prospective and retrospective studies and a favorable safety profile compared to conventional doxorubicin, which is associated with cardiotoxicity. [4][5][6]8 The most common treatment-related adverse events associated with PLD include palmar-plantar erythrodysesthesia and stomatitis. 4,6 The development of secondary malignancies, specifically squamous cell carcinoma (SCC) of the oral cavity, is recognized in patients treated with long-term PLD for Kaposi's sarcoma, desmoid tumor, recurrent uterine papillary serous carcinoma, and recurrent high-grade serous carcinoma, the majority of which are of ovarian origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation